2017
DOI: 10.21037/jtd.2017.05.04
|View full text |Cite
|
Sign up to set email alerts
|

Lung metastasectomy following kidney tumors: outcomes and prognostic factors from a single-center experience

Abstract: IntroductionRenal cell carcinoma (RCC) represents approximately 2% of all tumors, and about 30% of patients are affected by metastatic lesions at diagnosis (1,2). About 20% to 40% of patients develops a metastatic disease after nephrectomy (3) and lung is one of the sites most frequently affected by RCC metastases (second after liver) (4). Patients that receive no treatment for metastatic RCC (mRCC) have a 0-18% 5-year survival (5). Nonsurgical therapy for mRCC has limited efficacy, with a median overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
5
12
0
1
Order By: Relevance
“…Among 30 patients with GU metastases, there were 23 (76.6%) with metastatic renal cell carcinoma, 3 with bladder cancer, 2 with prostate cancer, and 2 with genital cancer. Similar high post-PM survival rates (5-year OS of 75%) in metastatic renal cell carcinoma have been reported by Meacci et al 14 We hypothesize that outstanding GU histology-associated OS rates observed in our cohort may be a sequel of a careful patient selection. Interestingly, our univariable Cox proportional hazard model analysis demonstrated that patients in the age of 66 years and older had significantly worse survival compared with the younger patients (5-year OS rate 33.6 vs. 54.8%, respectively; p ¼ 0.0007).…”
Section: Discussionsupporting
confidence: 90%
“…Among 30 patients with GU metastases, there were 23 (76.6%) with metastatic renal cell carcinoma, 3 with bladder cancer, 2 with prostate cancer, and 2 with genital cancer. Similar high post-PM survival rates (5-year OS of 75%) in metastatic renal cell carcinoma have been reported by Meacci et al 14 We hypothesize that outstanding GU histology-associated OS rates observed in our cohort may be a sequel of a careful patient selection. Interestingly, our univariable Cox proportional hazard model analysis demonstrated that patients in the age of 66 years and older had significantly worse survival compared with the younger patients (5-year OS rate 33.6 vs. 54.8%, respectively; p ¼ 0.0007).…”
Section: Discussionsupporting
confidence: 90%
“…In fact, lung IM had a 5-year OS of 82% compared with 50.4% without surgical resection. These results are similar to what was previously reported in the literature for CM (range 75% to 83.3%) [18,19]. Site-specific survival analyses were not conducted in previous studies evaluating IM [7,8,12].…”
Section: Figure 2bsupporting
confidence: 90%
“…Duration decreases with compromised immune response [9]. The five and 10-year overall survival rate following pulmonary metastasectomy for metastatic renal cancer was 83% and 41.7% respectively according to Chen et al [14]and 75% and 59% respectively according to Meacciet al [15].…”
Section: Discussionmentioning
confidence: 98%